Divergent regulatory T cell responses to high-dose methylprednisolone and tocilizumab in giant cell arteritis. Issue 133 (December 2022) - Scholz, Godehard A.; Fux, Michaela; Christ, Lisa; Iype, Joseena; Banz, Yara; Villiger, Peter M.
Highlights: The clinical data of the proof-of-concept-study about tocilizumab (TCZ) monotherapy after ultra-short glucocorticoid (GC) administration in giant cell arteritis (GCA) was published in The Lancet Rheumatology (https://doi.org/10.1016/S2665-9913(21)00152-1 ). In this manuscript we summarize and analyze the T cell data of the mentioned study: This is the first study analyzing circulating regulatory T cells in newly diagnosed GCA cases prior to GC administration. The study design allowed a comparative analysis of T cell responses to GCs and TCZ. The data suggests a different type of regulatory T cells being involved in control of disease.